DEVELOPMENT OF PLAGIARISM DETECTION APPLICATION ON THE TEXT DOCUMENTS USING RABIN-KARP ALGORITHM - Kadek Versi Yana (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This study was aimed to design and implement a plagiarism detection application on the Indonesian documents texts using Rabin-Karp algorithm. The input of this application such documents which have text file (*. txt, *. html, *. php, *. xml, *. doc, *. docx, *. rtf) and the output of this application is the percentage of similarity of two documents. The result of this study is an application which is called "PlagiaTor" which was developed by using Borland Delphi 7 programming language. This application was able to detect plagiarism synonym words on Indonesian language document. On the PlagiaTor application there were five processes to detect the similarity of two documents, there were: casefolding and tokenizing, filtering, synonym recognition, stemming and string matching. The testing was done by trying out cutting document in any part of that document then the words were replaced by that synonym of those words and using different k-gram. Based on the testing, could be obtained the result that the application was able to detect plagiarism on synonym word well.